Comparative Microbiomics Analysis of Antimicrobial Antibody Response between Patients with Lung Cancer and Control Subjects with Benign Pulmonary Nodules - Shome, Mahasish; Gao, Weimin; Engelbrektson, Anna; Song, Lusheng; Williams, Stacy; Murugan, Vel; Park, Jin G.; Chung, Yunro; LaBaer, Joshua; Qiu, Ji (Cancer epidemiology, biomarkers & prevention, 2023)
CT screening can detect lung cancer early but suffers a high false-positive rate. There is a need for molecular biomarkers that can distinguish malignant and benign indeterminate pulmonary nodules (IPN) detected by CT scan. We profiled antibodies against 901 individual microbial antigens from 27 bacteria and 29 viruses in sera from 127 lung adenocarcinoma (ADC), 123 smoker controls (SMC), 170 benign nodule controls (BNC) individuals using protein microarrays to identify ADC and BNC specific antimicrobial antibodies. Analyzing fourth quartile ORs, we found more antibodies with higher prevalence in the three BNC subgroups than in ADC or SMC. We demonstrated that significantly more anti-Helicobacter pylori antibodies showed higher prevalence in ADC relative to SMC. We performed subgroup analysis and found that more antibodies with higher prevalence in light smokers (≤20 pack-years) compared with heavy smokers (>20 pack-years), in BNC with nodule size >1 cm than in those with ≤1 cm nodules, and in stage I ADC than in stage II and III ADC. We performed multivariate analysis and constructed antibody panels that can distinguish ADC versus SMC and ADC versus BNC with area under the ROC curve (AUC) of 0.88 and 0.80, respectively. Antimicrobial antibodies have the potential to reduce the false positive rate of CT screening and provide interesting insight in lung cancer development. Microbial infection plays an important role in lung cancer development and the formation of benign pulmonary nodules.